2019
DOI: 10.1111/jcmm.14536
|View full text |Cite
|
Sign up to set email alerts
|

Different signalling in infarcted and non‐infarcted areas of rat failing hearts: A role of necroptosis and inflammation

Abstract: Necroptosis has been recognized in heart failure (HF). In this study, we investigated detailed necroptotic signalling in infarcted and non‐infarcted areas separately and its mechanistic link with main features of HF. Post‐infarction HF in rats was induced by left coronary occlusion (60 minutes) followed by 42‐day reperfusion. Heart function was assessed echocardiographically. Molecular signalling and proposed mechanisms (oxidative stress, collagen deposition and inflammation) were investigated in whole hearts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 66 publications
(125 reference statements)
4
29
0
Order By: Relevance
“…In spite of this experimental limitation, considering the decreased pSer229-RIP3 levels in the RV, it can be suggested, that despite MLKL upregulation, the post-MI pro-necroptotic environment in the LV spared the neighboring RV, at least in this stage of HF. Such an observation is in accordance with recent knowledge about necroptosis regulation, where particular changes in pSer229-RIP3 corresponded with p-MLKL, thereby indicating the presence or absence of necroptosis [ 7 , 8 , 13 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In spite of this experimental limitation, considering the decreased pSer229-RIP3 levels in the RV, it can be suggested, that despite MLKL upregulation, the post-MI pro-necroptotic environment in the LV spared the neighboring RV, at least in this stage of HF. Such an observation is in accordance with recent knowledge about necroptosis regulation, where particular changes in pSer229-RIP3 corresponded with p-MLKL, thereby indicating the presence or absence of necroptosis [ 7 , 8 , 13 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, we have shown the activation of canonical necroptosis signaling being implicated in both infarcted and non-infarcted LV areas of failing rat hearts, while its execution mechanisms were restricted to the former area only. Such activation of necroptotic signaling has been suggested to be associated with myocardial fibrosis, ventricular remodeling, inflammation and severe contractile dysfunction [ 8 ]. Likewise, studies employing explanted human failing hearts of various etiologies have shown the participation of necroptosis in HF-associated myocardial deterioration [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations